Towards sustainability : new approaches to nano-drug preparation - Cheow, Wean Sin (2014)
The conversion of drugs into drug nanoparticles (nano-drugs) represents a feasible method to enhance bioavailability of otherwise sparingly soluble-drugs. Nano-drugs enhance bioavailability through the improvement of dissolution rate and saturation solubility of drugs, by virtue of their small sizes. Nano-drugs available in the market are usually produced by top-down methods, such as wet milling and high pressure homogenization. These conventional top-down methods, however, suffer from high energy and time requirement, as well as wide and inconsistent nano-drug size distribution. Furthermore, commercially available nano-drugs are predominantly crystalline while amorphous nano-drugs are largely neglected despite their propensity to generate high saturation solubility. In this review, nonconventional methods to prepare crystalline and amorphous nano-drugs are discussed, with the bioavailability enhancing characteristics highlighted. Both top-down and bottom-up methods are covered, finally, a sustainability-based perspective comparing amorphous and crystalline nano-drugs is presented.